Structurally improved MgO adsorbents derived from magnesium oxalate precursor for enhanced CO2 capture. (15th October 2020) - Tan, Chang; Guo, Yafei; Sun, Jian; Li, Weiling; Zhang, Jubing; Zhao, Chuanwen; Lu, Ping
Highlights: MgO adsorbents were prepared from magnesium oxalate precursor for CO2 capture. Effects of calcination conditions on structure-performance relationships were studied. Calcination atmosphere and temperature significantly affected the CO2 adsorption performance. The desired MgO-C-500 adsorbent exhibited a high CO2 uptake of 5.09 mmol CO2 /g. Abstract: Facile, green and solvent-free fabrication of efficient MgO-based adsorbents is highly necessary for their intermediate-temperature CO2 capture applications. In this work, MgO adsorbents were prepared by calcining magnesium oxalate precursor under different calcination atmospheres and temperatures. N2 adsorption-desorption, X-ray diffraction, scanning electron microscope, high-resolution transmission electron microscopy and CO2 temperature programmed desorption were employed to study their physicochemical properties. CO2 adsorption performance was evaluated by testing the adsorbents in a dry stream containing 10%CO2 at a mild temperature of 200 °C. The influence of calcination conditions on their structure-performance relationships was investigated. Calcination atmosphere and temperature will significantly affect the microstructure and CO2 adsorption performance. Calcination in a flowing CO2 stream will endow the adsorbent with minimized MgO crystal size, and this will offer more O 2− active sites at the edges and corners for enhanced CO2 adsorption capacity. The precursor can hardly be completely decomposed at a lower calcination temperature to form porous structure, and the basic active sites available for CO2 adsorption are limited. A higher calcination temperature will result in sintering of MgO crystals, pore structure blockage and loss of the O 2− basic active sites, and CO2 adsorption capacity will therefore be reduced. The desired MgO-C-500 adsorbent calcined in a flowing CO2 stream at 500 °C exhibits the highest CO2 adsorption capacity of 5.09 mmol CO2 /g. The results will pave the way for developing highly efficient MgO adsorbents for separating CO2 from industrial exhaust gas.